Condiciones de trabajo y salud laboral de los trabajadores de las bloqueras de la comunidad Boliche, parroquia Pastocalle - Diseño de un programa de intervención en seguridad laboral para la zona. - Mesías Herrera, Nancy Alexandra (2014)
This research describes the working and health conditions of the workers of the brick factory located in Boliche community, Pastocalle parish. The goal of the research was based on the design of an Intervention Program of job security, and thus improve working conditions and promote the health of workers of the brick factories; for this purpose the following objectives were developed: define working conditions required for the performance of work activities in a safe manner; analyze the types of illnesses in order to determine their degree of involvement in workers of the brick factories. The research was based on the study of exploratory and descriptive field; the techniques used for data collection were observation and survey. Due to the feasibility and cooperation extended by the owners of the brick factories, the research could be performed with the whole universe under study, the observation was made in the 22 brick factories and the surveys were applied to 66 workers which were previously validated by professional experts in the field. The information obtained was analyzed and presented using tables and graphs where the poor working conditions of brick factories were evidenced as well as health conditions that come to suffer the workers; so there is the need for guidance and training on standards and technsques of job security which will help to improve their health conditions, for which the existence of Labor Occupational Health Program for Zone is necessary. Analyzing the entire context of the investigation, it is concluded that a continually monitor must be done to the brick factories in order to ensure continuous improvement on the issue of job security